(3cJGH MQH Hfi TYjHGf hcSQi ef CLd GLGQJge ddMQbI GHfI GdfYeGfs
(3ChdgG (B:s
(3MOKfG HTQ bGd cf GdfYeGf hcGf YScQ BSQi eGjfi Cda hcGf GdfYeGf Hf GdefJUQ Ydi NOeJg s
(3BNQgG (B:s
(3BNQ GdehLhO efg (B: (3abGdhG gPG ZdGe ddedc CeQ HUdHg hbUJg cPG hcPG aYfO Pdc JbOe UZjQ GdLQGejI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs